The Influence of Good Corporate Governance Mechanism, Corporate Social Responsibility and Intellectual Capital on Financial Performance with Profit Management as Mediation Variable in Various Industrial Sector Companies Listed on the Idx period 2017-2021 - Cut Alya Djafar; Kersna Minan; Liza Novietta (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of good corporate governance mechanism, corporate social responsibility, and intellectual capital on financial performance with earnings management as a mediating variable in companies in various industrial sectors on the Indonesian stock exchange for the period 2017 – 2021. This type of research is a quantitative research type. The population in this study are all companies in the various industrial sectors listed on the Indonesian stock exchange from 2017 – 2021. The sampling technique uses a purposive sampling method with a sample of 26 companies with 5 years of observation so that the total observational data is 130. The path analysis research design is used as a a tool to determine the direction of the variables studied and to justify how significant the influence of the independent and dependent variables is either directly or indirectly through mediating variables. The results of this study indicate that the mechanisms of good corporate governance, intellectual capital, and earnings management have a positive and significant effect on financial performance and Corporate Social Responsisbility has not significant effect on financial perfomance. Mechanisms of good corporate governance, corporate social responsibility, and intellectual capital also have a positive and significant effect on earnings management. Earnings management can mediate the effect of good corporate governance on financial performance. Earnings management can also mediate the effect of corporate social responsibility and intellectual capital on financial performance.